2018
DOI: 10.1103/physrevlett.120.215702
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Tricritical Point: A New Universality Class in Dirac Systems

Abstract: Tricriticality, as a sister of criticality, is a fundamental and absorbing issue in condensed-matter physics. It has been verified that the bosonic Wilson-Fisher universality class can be changed by gapless fermionic modes at criticality. However, the counterpart phenomena at tricriticality have rarely been explored. In this Letter, we study a model in which a tricritical Ising model is coupled to massless Dirac fermions. We find that the massless Dirac fermions result in the emergence of a new tricritical poi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 62 publications
(95 reference statements)
2
16
0
Order By: Relevance
“…To explain this observation, we develop a modified mean-field theory to study the effective coupling in the free energy and reveal that this anomalous phenomenon is induced by the interplay between critical fluctuations and the finite-size effects, in a quantitative manner. Moreover, we pinpoint the tricritical point separating the first-order and the continuous phase transitions, and numerically verify that this CTP acquires the critical exponents of chiral Gross-Neveu universality, confirming the renormalization group predictions 63 .…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…To explain this observation, we develop a modified mean-field theory to study the effective coupling in the free energy and reveal that this anomalous phenomenon is induced by the interplay between critical fluctuations and the finite-size effects, in a quantitative manner. Moreover, we pinpoint the tricritical point separating the first-order and the continuous phase transitions, and numerically verify that this CTP acquires the critical exponents of chiral Gross-Neveu universality, confirming the renormalization group predictions 63 .…”
Section: Introductionsupporting
confidence: 77%
“…Although enormous investigations have been devoted to this issue 35,[42][43][44][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] , the numerical verification for type-II FIQCP is still lacking. Remarkably, recent studies based on the fieldtheoretical effective model propose that type-II FIQCP can also feature new tricritical behaviors, controlled by the chiral tricritical point (CTP) 63 . This CTP separates the conventional Landau-Devonshire first-order transition from the type-II FIQCP 33 , and the universal scaling behavior near this CTP is quite different from its pure bosonic counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…The key features of the FRG approach in the present context are the following: The FRG is well-suited for calculations directly in 2+1 dimensions. It has been tested against other methods which has shown that it provides very good results in the context of Gross-NeveuYukawa models [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] . Importantly, the FRG approach already includes resummation effects through the non-perturbative threshold functions 61,62 , which is in contrast to perturbative approaches.…”
Section: A Methodsmentioning
confidence: 99%
“…The destoryed Fermi-liquid behavior can be observed by the singular Bosonic susceptibility at the nesting wavevector, and it can't be found even at low-energy limit (far away from the quantum critical point) when the ultraviolet cutoff applied is infinite during the calculation, as could be found in the many-electron system, for example, when the Fermions coupled to the 1D Ising variable [40] or the fluctuation transverse gauge field [41] or the longitudinal Bosonic excitation [2]. The non-Fermi-liquid phenomenons are widely observed in the heavy-Fermi system and the cuprate materials [42,43], including the logarithmic divergent specific heat which related to the free energy by…”
Section: Optical Conductivitymentioning
confidence: 99%